METHODOLOGY FOR QUALITY ASSESSMENT IN THE RAILWAY PASSENGER TRANSPORT - Nedeliakova, Eva; Dolinayova, Anna (Doprava a spoje, 2007)
The article deals with new methodology for quality assessment in the conditions of railway passenger transport. There are defined the indicators for specified criterions of quality services. The article describes one part of the marketing research, which is founded on designed criterions. Marketing research contains quality perception of transport services from two different points of view - customer and staff.